FACTORS INFLUENCING THAI EFL TEACHERS’ INTEGRATION OF DIGITAL TECHNOLOGY IN ENGLISH LANGUAGE TEACHING - Singsamran, Pornnarong; Chojit, Yuwadee (วารสารนิสิตวัง, 2026)
This mixed methods study aimed to (1) examine the current state of digital technology integration among Thai EFL teachers in primary schools under the Bangkok Metropolitan Administration (BMA), (2) identify and analyze factors influencing technology integration, (3) investigate the predictive power of these factors, and (4) explore teachers’ perceptions and lived experiences regarding barriers and facilitators of technology integration. The participants consisted of 400 English language teachers selected through stratified random sampling from 50 BMA primary schools. Quantitative data were collected using a validated questionnaire based on the Technology Acceptance Model (TAM) and related digital competence constructs, while qualitative data were gathered through semi-structured interviews with 20 purposively selected participants. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis, whereas qualitative data were analyzed through thematic analysis. In relation to the research objectives, the findings can be summarized as follows : First, the current state of digital technology integration among Thai EFL teachers in BMA primary schools was at a moderate level, with most teachers operating at the infusion and integration stages. Second, key factors influencing technology integration included digital competence, perceived usefulness, institutional support, and student motivation. Third, the predictive analysis demonstrated that these factors significantly contributed to technology integration, with digital competence being the strongest predictor, and the model explaining 61.3% of the variance. Finally, qualitative findings revealed that while teachers recognized the pedagogical value of digital technology, they faced challenges related to infrastructure, training, and time constraints, whereas professional learning communities and leadership support acted as important facilitating conditions.